2002
DOI: 10.2190/6k4g-lwpq-ray8-67qg
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Conveyed by Sound in the Poetry of Alfred, Lord Tennyson

Abstract: The use of sound was studied in several of Tennyson's shorter and better-known poems (e.g., Break, Break, Break and Ulysses) and in In Memoriam A. H. H. Poems were broken down into their component phonemes which were then classified in terms of their emotional character. The emotional character of sounds preferentially employed in each of the shorter poems matched the emotional theme of the poem (e.g., sounds employed in Airy Fairy Lilian and Lady of Shallot were most pleasant, those in Crossing the Bar were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Differences between poetic and prosaic language use can be based on the dominance of the poetic function including the focus on the message itself (Jakobson, 1960). Consequently, this determining function of the poetic genre influences all linguistic constituents of poetry and particularly its sound (Jakobson & Waugh, 1979/2002, that is, the phonological structures and their units: phonemes and syllables. Empirical results support the notion that literary foregrounded and hence deviating elements provoke a more intensive and extensive cognitive processing (van Peer, 1986) and deeper emotional experience (Miall & Kuiken, 1994).…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Differences between poetic and prosaic language use can be based on the dominance of the poetic function including the focus on the message itself (Jakobson, 1960). Consequently, this determining function of the poetic genre influences all linguistic constituents of poetry and particularly its sound (Jakobson & Waugh, 1979/2002, that is, the phonological structures and their units: phonemes and syllables. Empirical results support the notion that literary foregrounded and hence deviating elements provoke a more intensive and extensive cognitive processing (van Peer, 1986) and deeper emotional experience (Miall & Kuiken, 1994).…”
Section: The Present Studymentioning
confidence: 99%
“…Hitherto, research has either concentrated solely on the textual constituents (e.g., Albers, 2008) or put these in relation with results from survey studies (e.g., Auracher et al, 2010). Only a few studies have also paid attention to the poets-after all the creators of their stimuli-and where this was the case, only theoretical treatises or critical writings were considered (e.g., Whissell, 2002Whissell, , 2011.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…According to literary theory, this results in a pronounced “palpableness” of form (Jakobson, 1960 ) and, most notably, of the sound patterns in poetry (Shklovsky, 1919/2012 ; Jakobson and Waugh, 1979/2002 ). Theoretical reflections as well as empirical studies have repeatedly highlighted the relation between the sound of a poem and the perception of emotion by its readers (e.g., Valéry, 1958 ; Fónagy, 1961 ; Jakobson and Waugh, 1979/2002 ; Tsur, 1992 ; Whissell, 2002 , 2011 ; Schrott and Jacobs, 2011 ; Aryani et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent (psycho-)linguistic studies have suggested that phonological iconicity is a property of languages that should be acknowledged as an important addition to the principle of the arbitrariness of the linguistic sign (Perniss et al, 2010; Myers-Schulz et al, 2013; Perniss and Vigliocco, 2014; for an overview see Hinton et al, 2006; Schmidtke et al, 2014). In particular, poetry has often served as a testing ground for the hypothesis of an “inmost, natural similarity association between sound and meaning” (Jakobson and Waugh, 1979/2002, p. 182; see also Valery, 1958; Jakobson, 1960; Fónagy, 1961; Tsur, 1992; Whissell, 2002, 2011; Pope, 2010; Schrott and Jacobs, 2011; Aryani et al, 2016). Specifically, two studies by Albers (2008) and Auracher et al (2010) provided empirical support for the hypothesis of phono-emotional iconicity in poetry.…”
Section: Introductionmentioning
confidence: 99%